SPIRITUAL ACCOUNTABILITY IN AL-QURAN DONATION MANAGEMENT: JARIAH CHARITY PROJECT COMMUNITY - Zainal Potton; Alimuddin; Syarifuddin (ZILLZELL MEDIA PRIMA, 2026)
This study aims to understand the meaning of spiritual accountability in the management of Al-Qur'an donations within the Jariah Charity Project Community in Enrekang Regency. This research employs a qualitative approach with a phenomenological method to explore the experiences, understandings, and meanings constructed by administrators, volunteers, donors, and beneficiaries in donation management practices. The data were collected through in-depth interviews, observation, and documentation, and were analyzed through data reduction, coding, theme grouping, phenomenological interpretation, and conclusion drawing. The findings show that the management of Al-Qur'an donations is carried out through several stages, namely receiving donations, simple recording, procuring Al-Qur'an copies, distributing them to beneficiaries, and reporting to donors through documentation and direct communication. Spiritual accountability in this community is shaped by the values of trustworthiness, sincerity, transparency, hereafter accountability, and public benefit. Accounting practices in this context do not merely function as administrative recording tools, but also serve as a means of maintaining trust, fulfilling entrusted responsibilities, and being accountable to both human beings and Allah SWT. This study concludes that spiritual accountability in the management of Al-Qur'an donations represents a combination of social and spiritual responsibility, forming a simple yet meaningful accounting practice within a socio-religious community.